2022
DOI: 10.35219/awet.2022.08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GTAW on the Tensile Strength and Hardness of Mild Steel

Abstract: Gas tungsten metal arc welding (GTAW) is used to study the effect of the base metal thickness, welding current and welding speed on the tensile strength and hardness of mild steel welding. The analysis found that base metal thickness had the highest effect and highest means of tensile strength and hardness of the welding. Taguchi’s design (TD) suggested using higher base metal thickness, lower welding current and higher welding speed when welding mild steel in order to obtain maximum tensile strength and hardn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 8 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…The internal stresses have been reported to cause decreased hardness [34]. The decreased hardness was reported to result in lower transverse tensile strength [19,20,21]. This because the decreased hardness promotes ductility and thus decreased welding tensile strength.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The internal stresses have been reported to cause decreased hardness [34]. The decreased hardness was reported to result in lower transverse tensile strength [19,20,21]. This because the decreased hardness promotes ductility and thus decreased welding tensile strength.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between tensile strength and hardness was reported before [19,20,21]. Calderón et al (2021) concluded that the tensile strength and hardness of FZ and HAZ were also studied because they affect the mechanical properties of welding due to the different properties of the welding and adjacent regions [22].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations